2020
DOI: 10.1021/acsomega.0c00204
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Evolution over Exfoliated Rh-Doped Titanate Nanosheets

Abstract: Various amounts of Rh-doped titanate nanosheets (Ti3NS:Rh­(x), where x is doped amount) were prepared to develop a new nanostructured photocatalyst based on metal oxide compounds that can split water to produce H2 under sunlight. Ti3NS:Rh­(x) was obtained by acid exchange, intercalation, and exfoliation of Rh-doped layered sodium titanate compound (Na2Ti3–x Rh x O7). A new energy gap was found in the diffuse reflection spectrum of the Ti3NS:Rh­(x) colloidal suspension solution; this new energy gap corresponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…Similarly, Huang et al have also found that Rh­(IV) is the more dominating species as per their XPS data . It is known that the intrinsic electrons at Rh­(III) sites can be excited to the conduction band of TiO 2 for HER by visible light, while Rh­(IV) sites tend to trap electrons and incur recombination with holes . Therefore, the latter is regarded as a liability to be avoided.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, Huang et al have also found that Rh­(IV) is the more dominating species as per their XPS data . It is known that the intrinsic electrons at Rh­(III) sites can be excited to the conduction band of TiO 2 for HER by visible light, while Rh­(IV) sites tend to trap electrons and incur recombination with holes . Therefore, the latter is regarded as a liability to be avoided.…”
Section: Resultsmentioning
confidence: 81%
“…18 It is known that the intrinsic electrons at Rh(III) sites can be excited to the conduction band of TiO 2 for HER by visible light, while Rh(IV) sites tend to trap electrons and incur recombination with holes. 19 Therefore, the latter is regarded as a liability to be avoided. Nevertheless, as revealed next, doping even in the form of Rh(IV) may have benefits.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rh-Ti3NS Solid-state reaction method, water solution (pH triethylamine (TEA) as an electron donor, 500 W Xe lamp, λ > 220 nm 1970 μmolg -1 h -1 [145] Pt@Cu1.94S−ZnxCd1−xS 1D, 0≤x≤1…”
Section: Loading Of Cocatalyst Below Optimal Amountmentioning
confidence: 99%
“…However, the majority of the tungstates only act in the ultraviolet zone . To improve the photocatalytic activities of the famous g-C 3 N 4 and titanate photocatalysts, the common way is to dope elements into their crystal structures. , Herein, we introduced a visible-light-responsive Ce-doped SrWO 4 sample as a photocatalyst for the application of Cr­(VI) reduction. In this paper, a photocatalytic reduction of a Cr 2 O 7 2– (10 ppm) aqueous solution was carried out in the presence of a methanol solution (8 vol %) under simulated sunlight.…”
Section: Introductionmentioning
confidence: 99%